Supramolecular Phosphorescent Trinuclear Copper(I) Pyrazolate Complexes for Vapochromic Chemosensors of Ethanol - Hendrik Oktendy Lintang; Nur Fatiha Ghazalli; Leny Yuliati (Indonesian Journal of Chemistry, 2017)
We highlight that by using supramolecular single crystals of phosphorescent trinuclear copper(I) pyrazolate complexes with different molecular structures (2A-E), vapochromic chemosensors were successfully designed for sensing ethanol with high sensing capability. These complexes 2A-E were synthesized from non-side chain, 3,5-dimethyl, 3,5-bis(trifluoromethyl), 3,5-diphenyl and 4-(3,5-dimethoxybenzyl)-3,5-dimethyl pyrazole ligands (1A-E) in 83, 97, 99, 88 and 85% yields, respectively. All complexes showed emission bands centered at 553, 584, 570 and 616 nm upon an excitation at 280 nm for complexes 2A-C,E, respectively and 642 nm upon an excitation at 321 nm for complex 2D with lifetime in microseconds, indicating a large Stoke shift for phosphorescent compounds. These emission spectra were in good agreement with their colors from green to red upon exposure to a UV lamp with an excitation at 254 nm in dark room. Upon exposure to ethanol in 5 min, quenching, photoinduced energy transfer and shifting of emission intensities were observed for chemosensors 2A-C, 2D and 2E, respectively. Interestingly, chemosensor 2E only showed completely and autonomously recovery of its original emission intensity. Such novel finding in sensing capability might be caused by a weak intermolecular hydrogen bonding interaction of ethanol to oxygen atoms at dimethoxybenzyl side-chains of the pyrazole ring.